Connexin-Based Therapeutics and Tissue Engineering Approaches to the Amelioration of Chronic Pancreatitis and Type I Diabetes: Construction and Characterization of a Novel Prevascularized Bioartificial Pancreas - J. Matthew Rhett; Hongjun Wang; Heather Bainbridge; Lili Song; Michael J. Yost (Journal of Diabetes Research)
Total pancreatectomy and islet autotransplantation is a cutting-edge technique to treat chronic pancreatitis and postoperative diabetes. A major obstacle has been low islet cell survival due largely to the innate inflammatory response. Connexin43 (Cx43) channels play a key role in early inflammation and have proven to be viable therapeutic targets. Even if cell death due to early inflammation is avoided, insufficient vascularization is a primary obstacle to maintaining the viability of implanted cells. We have invented technologies targeting the inflammatory response and poor vascularization: a Cx43 mimetic peptide that inhibits inflammation and a novel prevascularized tissue engineered construct. We combined these technologies with isolated islets to create a prevascularized bioartificial pancreas that is resistant to the innate inflammatory response. Immunoconfocal microscopy showed that constructs containing islets express insulin and possess a vascular network similar to constructs without islets. Glucose stimulated islet-containing constructs displayed reduced insulin secretion compared to islets alone. However, labeling for insulin post-glucose stimulation revealed that the constructs expressed abundant levels of insulin. This discrepancy was found to be due to the expression of insulin degrading enzyme. These results suggest that the prevascularized bioartificial pancreas is potentially a tool for improving long-term islet cell survival in vivo.